Why relational marketing impacts on bank's customer satisfaction? - Dedy Ansari Harahap; Dita Amanah; Rubayah Yakob (BISMA (Bisnis dan Manajemen), 2019)
This study examines the impact of relational marketing to customer satisfaction with the case study on Postgraduate Students at Universitas Pendidikan Indonesia who become the customer of Bank BNI Setiabudhi, Bandung. The study aims to determine the impact of relational marketings variables such as the level of commitment, empathy, reciprocity and trust to customer satisfaction. The research method is an explanatory research with probability sampling as the sampling method. There are 110 samples that collected through questionnaire. The samples are randomly selected and measured by Likert scale. Furthermore, the data is analyzed  with Multiple Linier Regression methods. The result of study implies that the variables of relational marketing impact positively to the level of customer satisfaction. The dimension of œtrust gives the strongest effect on customer satisfaction and the dimension of œempathy gives the weakest effect on customer satisfaction.KeywordsBank; customers; relational marketing; satisfaction